Parasitological and Molecular Observations on a Little Family Outbreak of Human Fasciolosis Diagnosed in Italy - Gabrielli, Simona (Hindawi Publishing Corporation, 2014)
In the year 2010, three children who were born in a Romanian cattle farmer family went to Italy to join their mother. One of them was admitted to an Italian pediatric hospital for severe anemia that, when she was in her country, had been treated with blood transfusion. Blood tests and an abdominal ultrasound study triggered the suspicion of biliary parasitosis. The child underwent a cholangiopancreatography that caused the release of parasitic material microscopically identified as Fasciola hepatica. All children and their mother were submitted to coproparasitological analyses, which identified F. hepatica eggs only in the patient and in her twin sister. Parasitic materials recovered and flatworm specimens by us ad hoc obtained from Italian and Romanian cattle were genetically (ITS and COI genes) analyzed, and their sequences were compared with those deposited in GenBank. Specimens from children clustered with the Romanian strain examined and showed remarkable genetic differences with flatworm specimens from Italy. Anamnesis, parasite biology, and genetic data strongly suggest that twin sisters became infected in Romania; however, human fasciolosis is an emerging sanitary problem, favored by climate changes and global drivers; therefore, it deserves more attention on behalf of physicians working in both developing and developed countries.